POLICY ANALYSIS OF SCHOOL PRINCIPALS IN PREPARING THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM IN ELEMENTARY SCHOOLS (EP 7: DRIVING SCHOOL PROGRAM) - Yani Pratiwi; Sutrisno Sutrisno (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
As a leader in an educational institution, the principal is one of the determining factors that can encourage schools to realize the vision, mission, goals, and objectives through various programs that are implemented in a planned manner. Therefore, this study will analyze the principal's policy in preparing for the implementation of the independent curriculum at Palembang 104 Public Elementary School and what efforts are made by the principal to make it easier for teachers to develop and apply the independent curriculum. This study used a qualitative research method based on field research or field research. The research was conducted at SDN 104 Palembang and the research objects were the principal and teachers. The obstacles to preparing for the implementation of the independent curriculum, such as inadequate facilities, teacher readiness, and education regarding the independent curriculum for teachers. Regarding the statement from the Ministry of Education and Culture that SDN 104 Palembang does not have to wait for all the teachers to be ready, because its implementation in elementary schools is only recommended for grades 1 and 4. The facilities are not difficult, schools and parents can take part in determining the material to be focused on students, and parents can help if such facilities are not available at school.